The Role of Cytokines and Chemokines in Severe Acute Respiratory Syndrome Coronavirus 2 Infections - Hsu, Ren-Jun; Yu, Wei-Chieh; Peng, Guan-Ru; Ye, Chih-Hung; Hu, SuiYun; Chong, Patrick Chun Theng; Yap, Kah Yi; Lee, Jamie Yu Chieh; Lin, Wei-Chen; Yu, Shu-Han (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in countless infections and caused millions of deaths since its emergence in 2019. Coronavirus disease 2019 (COVID-19)-associated mortality is caused by uncontrolled inflammation, aberrant immune response, cytokine storm, and an imbalanced hyperactive immune system. The cytokine storm further results in multiple organ failure and lung immunopathology. Therefore, any potential treatments should focus on the direct elimination of viral particles, prevention strategies, and mitigation of the imbalanced (hyperactive) immune system. This review focuses on cytokine secretions of innate and adaptive immune responses against COVID-19, including interleukins, interferons, tumor necrosis factor-alpha, and other chemokines. In addition to the review focus, we discuss potential immunotherapeutic approaches based on relevant pathophysiological features, the systemic immune response against SARS-CoV-2, and data from recent clinical trials and experiments on the COVID-19-associated cytokine storm. Prompt use of these cytokines as diagnostic markers and aggressive prevention and management of the cytokine storm can help determine COVID-19-associated morbidity and mortality. The prophylaxis and rapid management of the cytokine storm appear to significantly improve disease outcomes. For these reasons, this study aims to provide advanced information to facilitate innovative strategies to survive in the COVID-19 pandemic.